(untitled) (INTEGRATION PROCEEDING, 2023)
Domestic violence is an act committed against other people, especially women, which causes physical, sexual,emotional pain or suffering or neglect of the family. Domestic violence can lead to risks or bad impacts in all aspectsof life that will last a long time. The risk of suicide is increasing, even from a global record, 800 thousand adults wantto commit suicide every year. This research is to find out about the relationship between domestic violence andwomen to the risk ofsuicide in the Terminal Health Center Work Area. This study uses quantitative research usingcross-sectional. The sample is part of the population, amounting to 83 people, the time needed to distribute thequestionnaires is one week. Sampling technique in this research used accidental sampling. The result of the study ofthe Chi-quare test showed that the results of this study showed that out of 83 respondents indicated a very high risk of committing suicide (75.9%) and occurrence of domestic violence (72.30%). p-value 0.00%> 0.005%.Therefore, there is a Relationship between Domestic Violence in Women and the Risk of Suicide.